A new species of Ophlomisidium (Echinodermata : Ophiuroidea) from the continental shelf and slope off southern Brazil - Borges, Michela; Monteiro, Ana Maria G.; Amaral, A. Cecilia L. (Cambridge University Press, 2006)
A new species of Ophiomisidium is described and regards about reproduction are presented. It is the first species in the genus to posses, apparently,. a brooding development. Very few specimens of species of Ophiomisidium have previously been collected, but over 3000 specimens of the new species were collected on the continental shelf and slope (60-810 m depth) off southern Brazil. They were obtained during the REVIZEE Programme, the first extensive surveys to examine Brazilian ophiuroids from depths greater than 200 m.